2022
DOI: 10.1063/5.0118097
|View full text |Cite|
|
Sign up to set email alerts
|

Hemodynamic characteristics in a cerebral aneurysm model using non-Newtonian blood analogues

Abstract: This study aims to develop an experimentally validated computational fluid dynamics (CFD) model to estimate hemodynamic characteristics in cerebral aneurysms (CAs) using non-Newtonian blood analogues. Blood viscosities varying with shear rates were measured under four temperatures firstly, which serves as the reference for the generation of blood analogues. Using the blood analogue, particle image velocimetry (PIV) measurements were conducted to quantify flow characteristics in a CA model. Then, using the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 85 publications
2
15
0
Order By: Relevance
“…Due to the sensitivity to initial conditions and global hydrodynamic instability, it has been found that the physiologic pulsatile blood flow is turbulent even under a relatively small mean Reynolds number in both studies in vitro and in silico ( Valen-Sendstad et al, 2011 ; Yagi et al, 2013 ; Jain et al, 2016 ; Saqr et al, 2020 ; Tupin et al, 2020 ; Yi et al, 2022b ). Thus, the continuity and momentum equations can be written in tensor form, i.e., where represents the blood flow velocity, p is the pressure, is the gravity, is the blood dynamic viscosity which was set as in accordance with the PIV tests, and is the turbulent viscosity.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Due to the sensitivity to initial conditions and global hydrodynamic instability, it has been found that the physiologic pulsatile blood flow is turbulent even under a relatively small mean Reynolds number in both studies in vitro and in silico ( Valen-Sendstad et al, 2011 ; Yagi et al, 2013 ; Jain et al, 2016 ; Saqr et al, 2020 ; Tupin et al, 2020 ; Yi et al, 2022b ). Thus, the continuity and momentum equations can be written in tensor form, i.e., where represents the blood flow velocity, p is the pressure, is the gravity, is the blood dynamic viscosity which was set as in accordance with the PIV tests, and is the turbulent viscosity.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…To explore hemodynamic patterns in MT models, our experimental validated non-Newtonian CFD CA model [8] was employed to simulate the blood flow regime. The unsteady and periodic pulsatile incompressible blood flow can be modeled by the continuity and momentum equations, which are, i.e., 𝛻 • 𝑣 ⃗ = 0…”
Section: Mathematical Equationsmentioning
confidence: 99%
“…where 𝑣 ⃗ is the blood velocity vector, 𝑝 is the pressure, 𝑔 ⃗ is gravity vector, and 𝜌 denotes blood density. In this study, 𝜌 (i.e., 1050 kg/m 3 ) is adopted for the CFD simulations, 𝜇 is blood viscosity determined by a non-Newtonian viscosity model at temperature 310.15 K (see Figure 7) which was developed in our previous publication [8]. Specifically, the model is expressed by, i.e.,…”
Section: Mathematical Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the statistical data from the World Health Organization, cardiovascular associated diseases have become the topmost cause of death [ 1 , 2 ], and it has been identified that hemodynamic factors play a significant role in the development and progression of such diseases [ 3 , 4 , 5 , 6 ]. For example, the development of atherosclerosis is based on the observation that vascular inflammation and plaques are distributed near side branches or arterials stenosis, where blood flow is non-uniform, and at the lesser curvature of bends where the blood flow rate is relatively low [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%